Effect of Soaking Time on the Pasting Properties of Two Cultivars of Trifoliate Yam (Dioscorea dumetorum) Flours - Abiodun, Olufunmilola Adunni; Adegbite, Jacob Adeyosoye; Oladipo, Tajudeen Solagbade (Pakistan Journal of Nutrition, 2009)
This study was carried out to determine the effect of soaking time on the pasting properties of two cultivars of trifoliate yam flour. The tubers were peeled, washed, sliced and kept under running tap water for 30, 60, 90 and 120 min. They were dried at 50 °C for 48 h. The dried samples were milled, sieved (600 μm) and packaged. Pasting properties were determined using Rapid Visco Analyzer and statistical analysis was carried out to test for significant difference (p < 0.05) using one way analysis of variance (ANOVA). Among the white cultivar samples, the sample WH60 had the highest peak viscosity, holding strength and final viscosity of 87.93, 68.34 and 128.34 RVU, respectively. Breakdown value of the untreated white sample (WHR) was significantly different (p < 0.05) from other white samples. There were no significant differences (p < 0.05) in setback values for samples soaked for 60, 90 and 120 min. Also, the yellow cultivar follow the same trend with the sample YL60 having the highest peak viscosity, holding strength, breakdown value and final viscosity of 80.32, 73.39, 6.93 and 138.15 RVU, respectively. Setback value for sample YL90 was significantly different (p < 0.05) from other samples. Pasting temperature and pasting time ranged from 74.25-76.60 °C and 4.62-5.35 min, respectively. Among the two cultivars, WH60 had the highest peak viscosity while YL60 had the highest holding strength and final viscosity. The yellow samples had lower breakdown values than the white samples. The flour samples from the two cultivars can be used in the food industries for baking and as thickeners.